2017
DOI: 10.1007/s00417-017-3697-7
|View full text |Cite
|
Sign up to set email alerts
|

CTG18.1 repeat expansion may reduce TCF4 gene expression in corneal endothelial cells of German patients with Fuchs’ dystrophy

Abstract: The CTG18.1 repeat expansion may reduce gene expression of TCF4 and ZEB1, suggesting that a mechanism triggering a loss of function may contribute to FECD. The correlation of CTG18.1 repeat expansion from blood and the cornea may represent the first step toward investigating the potential relevance of testing the blood of cornea donors to minimize the risk of transplanting grafts potentially affected with FECD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 45 publications
1
32
0
1
Order By: Relevance
“…Marker alleles were not found in 21 FECD patients; thus, exome sequencing for those particular patients is warranted. 18,19,22,35 76.4-77.0 21,26 17.3-34.1 37,40 43.9 41 25.5 42 72…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marker alleles were not found in 21 FECD patients; thus, exome sequencing for those particular patients is warranted. 18,19,22,35 76.4-77.0 21,26 17.3-34.1 37,40 43.9 41 25.5 42 72…”
Section: Discussionmentioning
confidence: 99%
“…Association of the intronic single-nucleotide Copyright 2018 The Authors iovs.arvojournals.org j ISSN: 1552-5783 polymorphism (SNP) rs613872 with FECD was discovered in the Genome-Wide Association Study (GWAS) performed by Baratz et al 12 Later, this association was confirmed in a number of studies involving more than a thousand people. [13][14][15][16][17][18][19][20][21] Other SNPs in the TCF4 gene are associated with FECD but to a lesser extent, namely, rs17595731, rs9954153, and rs2286812. 12,14,15 Wieben et al 22 found another important relationship between FECD and the expansion of trinucleotide repeats in the TCF4 gene intron CTG18.1: The expansion of trinucleotide repeats appeared to be a more specific marker of FECD than rs613872 (96% vs. 79%).…”
mentioning
confidence: 99%
“…Interestingly, an increase in the levels of TCF4 transcripts encoded by downstream alternative 5′ exons distal to the CTG TNR was also noted, which may indicate a compensatory mechanism to rescue the levels of TCF4 protein arising from the deficit of transcripts encoding TCF4-C. This compensation phenomenon needs to be considered when studying TCF4 expression levels in FECD and other diseases connected with the TCF4 intronic CTG TNR and could explain why different research groups have published contradictory results concerning changes in TCF4 levels when studying FECD 19 22 . Our results indicate that the levels of TCF4 transcripts change bidirectionally in response to an expanded CTG TNR—transcripts beginning near the repeat region decline just as Foja et al reported 19 while certain transcripts beginning downstream of the repeat region increase as reported here, and mask the decrease of long TCF4 transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…This compensation phenomenon needs to be considered when studying TCF4 expression levels in FECD and other diseases connected with the TCF4 intronic CTG TNR and could explain why different research groups have published contradictory results concerning changes in TCF4 levels when studying FECD 19 22 . Our results indicate that the levels of TCF4 transcripts change bidirectionally in response to an expanded CTG TNR—transcripts beginning near the repeat region decline just as Foja et al reported 19 while certain transcripts beginning downstream of the repeat region increase as reported here, and mask the decrease of long TCF4 transcripts. As the expression of different TCF4 transcripts decline and rise simultaneously the overall TCF4 levels may not change significantly in FECD as has been reported by Mootha et al 21 and Ołdak et al 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation